Analysis Of Economic Efficiency On Applied Of Synchronization Technology In Dairy Cows At Small Farmers - Supardi Rusdiana; Umi Adiati; Diana Andrianita Kusumaningrum; Chalid Talib (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
Abstract